Strengths of community and health facilities based interventions in improving women and adolescents’ care seeking behaviors as approaches for reducing maternal mortality and improving birth outcome among low income communities of Egypt - Metwally, Ammal M.; Abdel-Latif, Ghada A.; Mohsen, Amira; El Etreby, Lobna; Elmosalami, Dalia M.; Saleh, Rehan M.; El-Sonbaty, Marwa M.; Amer, Hala A.; El Deeb, Sherif E.; Fathy, Asmaa M.; Hanna, Carine; Azmy, Osama; et al. (BMC health services research, 2020)
Provision of emergency obstetric care is considered the key for maternal mortality reduction worldwide. This study evaluated the impact of community- and facility-based educational programs on provision of emergency obstetric care in Egypt. The study focused on evaluating utilization of the available health services and care seeking behaviors of mothers in the childbearing period. We implemented a package of community- and facility-focused educational interventions in two of Egypt's lowest income governorates. At facility level, health professionals at rural health units from 21 villages over 5 years were trained. Mass media gathering, individual teaching at health facilities, printed materials and home-based care sessions were provided. Collectively, these interventions were designed to focusing on recognition of the early warning signs during pregnancy, delivery and postpartum period for timely referral to hospitals for 20,494 women and adolescents mothers. The impact of the interventions was highly reflected on the percent of mothers received care during their pregnancy period. Proper antenatal care at governmental or private health facilities was raised dramatically from 0.6 to 59.3% and those who utilized at least one family planning method from 61.4 to 74.4%. Accordingly, the rate of complications significantly reduced during pregnancy (38.1 to 15.1%), during delivery (24.1 to 13.1%) and during postpartum (81.7 to 7.0%). As an impact to the improvement, there was a marked reduction in adolescent pregnancy by 55% and better birth outcome with a reduction in the percent of stillbirth by 11.5%. It is important to provide a comprehensive package that works at both improving qualities of care as well as empowering women by knowledge to first aid measures at the community level. The cost-effective way to empower mothers to provide first aid measures as emergency obstetric care is to adopt the outreach approach which could be more influential than mass media campaigns for the at-risk and vulnerable and low-income communities.